Building Leadership Skills in Research Groups. Issue 6 (25th June 2022) - Robel, Stefanie
Abstract: The academic research enterprise currently suffers from a culture of "academic bullying" and an unprecedented worldwide mental health crisis among trainees and faculty. These struggles, in part, result from a lack of leadership skills. Mental health, well‐being, intrinsic motivation, and engagement at work are linked to three fundamental needs of self‐determination: autonomy, competence, and relatedness. A great leader will first ensure they are meeting their own needs and, secondly, will support their team members in increasing their needs without decreasing autonomy. This article is a practical "how‐to" guide for researchers at every stage of the academic career path. It distinguishes management from leadership and addresses three key leadership competencies related to the self‐determination needs: 1. Increasing one's personal power as a foundation for autonomy, 2. building a culture of belonging and psychological safety to nurture relatedness, and 3. supporting and encouraging the need for competence by enabling people to self‐evaluate performance and direct professional growth. © 2022 Wiley Periodicals LLC.